2016
DOI: 10.1186/s12882-016-0260-4
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 attenuates the progression of renal dysfunction by blocking endothelial-to-mesenchymal transition in the 5/6 nephrectomy rat model

Abstract: BackgroundEndothelial-to-mesenchymal transition (EndoMT) is a crucial event during kidney interstitial fibrosis and it is believed to be inhibited by netrin-1. Our aim was to determine the influence of netrin-1 on renal EndoMT in chronic kidney disease by studying its effect in 5/6 nephrectomized (Nx) rats.MethodsMale Sprague–Dawley rats were divided into three groups (10 rats/group): sham-operated rats treated with control adenovirus; 5/6 Nx rats treated with control adenovirus; and 5/6 Nx rats treated with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Here, we observed that CKD was associated with a decrease in glomerular endothelial cell and podocyte density as reported previously (Sup Fig. 5A,B) 44,45 . miR299a-5p inhibition significantly preserved podocytes (Sup Fig.…”
Section: Tgfβ1-dependent Repression Of Fst Is Mediated By Mir299a-5psupporting
confidence: 89%
“…Here, we observed that CKD was associated with a decrease in glomerular endothelial cell and podocyte density as reported previously (Sup Fig. 5A,B) 44,45 . miR299a-5p inhibition significantly preserved podocytes (Sup Fig.…”
Section: Tgfβ1-dependent Repression Of Fst Is Mediated By Mir299a-5psupporting
confidence: 89%
“…Renal interstitial fibrosis (RIF) is a final common pathway for progression of all the various chronic kidney diseases (CKD) to end-stage renal disease (ESRD), causing the need of continuous renal replacement therapy in form of dialysis or transplantation (1). The main features of RIF, including renal tubular atrophy/dilatation, interstitial inflammatory cell infiltration, induction of apoptosis, fibroblasts activation and extracellular matrix (ECM) deposition, have been previously described (2).…”
Section: Introductionmentioning
confidence: 99%
“…Other signaling cascades and factors that abrogate EndMT include: (i) activation of the Src signaling pathway by hydrogen sulfide during endoplasmic reticulum (ER) stress [76]; (ii) glucagon-like peptide-1 (GLP-1) suppression of hyperglycemia-induced EndMT via reduced expression of ROS and inhibition of ROS-activated poly(ADP-ribose) polymerase 1 (PARP-1) [77]; (iii) high-density lipoprotein (HDL) inhibition of TGF-β1-induced EndMT [78]; (iv) endothelial heat shock protein beta-1 (HSPB-1)-mediated EndMT inhibition after stimulation with fibrotic cytokines [79]; (v) netrin-1-mediated attenuation of EndMT during renal dysfunction, as demonstrated in a nephrectomy rat model [80]; (vi) expression of ECM protein fibulin-1 via reduced expression of TGF-β2 [81]; (vii) secretion of cytokines and angiogenic factors by macrophages sustains endothelial differentiation of EPCs and consequently restricts EndMT during muscle regeneration [82].…”
Section: Introductionmentioning
confidence: 99%